2019
DOI: 10.1186/s12986-019-0338-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates oxidative injury in human umbilical vein endothelial cells through regulating mitochondrial fusion via TyrRS-PARP1 pathway

Abstract: Background/aimsOxidative stress-induced damage in endothelial cells is a crucial initiator of atherosclerosis (AS), which is highly related to excessive reactive oxygen species (ROS) and mitochondrial dynamics. Resveratrol (RSV) exerts beneficial effects against endothelial oxidative injury, while the underlying mechanisms have not been fully elucidated. Thus, we aimed to explore the role of mitochondria dynamics during the anti-oxidative activities of RSV in palmitic acid (PA)-stimulated human umbilical vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Moreover, the concentrations applied in our study were in line with some previously published works [8, 36]. Autophagy is a cellular housekeeping process involved in the turnover of cytoplasmic organelles and proteins through a lysosome-dependent degradation process, and it plays a critical role in cancers, neurodegenerative disorders, and cardiovascular diseases [3739]. Autophagy has been described as a major cytoprotective mechanism associated with phytochemicals [40].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the concentrations applied in our study were in line with some previously published works [8, 36]. Autophagy is a cellular housekeeping process involved in the turnover of cytoplasmic organelles and proteins through a lysosome-dependent degradation process, and it plays a critical role in cancers, neurodegenerative disorders, and cardiovascular diseases [3739]. Autophagy has been described as a major cytoprotective mechanism associated with phytochemicals [40].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, it inhibits excessive mitochondrial fission, restores the MMP, and inhibits apoptosis in HUVECs. The regulatory effect of resveratrol on mitochondrial fission/fusion and its protective effect on endothelial cells were affected by siRNA interference of TyrRS and PARP1 , indicating that resveratrol regulates mitochondrial fission/fusion through TyrRS-PARP1 signalling [ 63 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Moreover, our discovery of TyrRS being a biologically significant and physiologically relevant target of RSV that facilitates the conversion of trans-RSV to cis-RSV suggests that the cis-isomer of RSV is also a major isomer that evokes protective stress response. Other recent studies have also confirmed the TyrRS-PARP1 signaling in mediating the protective effects of RSV [120,229,296,[432][433][434]. However, there are still critical gaps in our knowledge.…”
Section: Cisand Trans-rsv Have Opposite Effects On Tyrrs-regulated Pamentioning
confidence: 92%
“…Activation of SIRT1 sensitizes neurons to oxidative stress [221,222] and inhibits neurogenesis [223] while RSV protects neurons against oxidative stress [224,225] and enhances neurogenesis [226,227]. Similarly, activation of SIRT1 promotes mitochondrial fission [228], and treatment with RSV rather enhances mitochondrial fusion [229]. Similarly, although brain-specific activation of SIRT1 drives anxiety and exploratory drive [48,230], RSV rather protects against autistic features [231][232][233][234].…”
Section: Rsv Is Also An Indirect Inhibitor Of Sirt1mentioning
confidence: 99%
See 1 more Smart Citation